2014
DOI: 10.1155/2014/985373
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mediterranean Diet Intervention on Dietary Glycemic Load and Dietary Glycemic Index: The PREDIMED Study

Abstract: Objective. To compare the one year effect of two dietary interventions with MeDiet on GL and GI in the PREDIMED trial. Methods. Participants were older subjects at high risk for cardiovascular disease. This analysis included 2866 nondiabetic subjects. Diet was assessed with a validated 137-item food frequency questionnaire (FFQ). The GI of each FFQ item was assigned by a 5-step methodology using the International Tables of GI and GL Values. Generalized linear models were fitted to assess the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Therefore, it is possible also that the MD indirectly improves cognitive function by lowering the risk of well-established risk factors. Moreover, certain components of the MD, such as legumes and whole-grain foods, may have indirect effects on cognition through their lower glycemic indexes, leading to reductions in blood glucose oscillations compared with those of a typical Western diet (77). As discussed in a previous systematic review, the effect of a long-term low-glycemic index diet on cognitive function in adults needs to be explored further (78).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible also that the MD indirectly improves cognitive function by lowering the risk of well-established risk factors. Moreover, certain components of the MD, such as legumes and whole-grain foods, may have indirect effects on cognition through their lower glycemic indexes, leading to reductions in blood glucose oscillations compared with those of a typical Western diet (77). As discussed in a previous systematic review, the effect of a long-term low-glycemic index diet on cognitive function in adults needs to be explored further (78).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Mediterranean diet is characterized by a high intake of exogenous dietary phenolics as a consequence of a high intake of virgin olive oil (VOO), fruit, nuts, vegetables, and cereals; a moderate intake of fish and poultry; a low intake of dairy products, red meat, processed meats, and sweets; and wine in moderation, consumed with meals [2]. Results from the Prevention with Mediterranean Diet (PREDIMED) study showed that the higher phenolic intake of the Mediterranean diet is associated with a lower incidence of cardiovascular diseases, metabolic syndrome, cancer and age-related cognitive decline [3,4,5,6,7,8,9,10,11]. …”
Section: Market Needs For Functional Oilsmentioning
confidence: 99%
“…Low-GI foods, although recommended for diabetes control by many diabetes agencies, 12–14 23 have not been tested specifically on vascular outcomes despite cohort studies suggesting that low-GI diets, especially in women, are associated with reduced CVD. 24 Additionally, a randomised trial, the PREDIMED study, that reduced the GI and GL of the diet 25 and included the use of nuts and olive oil to achieve this effect also reduced CVD, especially stroke. 26 We have demonstrated the greater effectiveness of low-GI diets in reducing HbA1c and blood pressure in T2DM.…”
Section: Introductionmentioning
confidence: 99%